2021
DOI: 10.1177/23780231211009991
|View full text |Cite
|
Sign up to set email alerts
|

Decline in Rate of Divorce and Separation Filings in Denmark in 2020 Compared with Previous Years

Abstract: The radical changes to everyday life brought on by the coronavirus disease 2019 (COVID-19) pandemic and the closure of nonfamily social spheres in particular may have impacted marriage dynamics. The author provides evidence on the monthly rates of initiation of divorce and separation filings in Denmark for the period from 2016 to 2020 to examine how filing behavior changed during 2020 compared with the four previous years. Because filing precedes divorce, rates reflect more precisely the temporal dynamic of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…Our findings in Mexico, a middle-income setting, suggest a similar decline in new marriages and new divorces. However, Mexico’s decline in new marriages (54%) and divorces (43%) is substantial when compared with related studies in high-income countries, which range from a reduction in new divorces by 3% to 27% and new marriages by 10% to 14% (Fallesen, 2021 , Kim & Kim, 2021 , Komura & Ogawa, 2022 , Westrick-Payne et al, 2022 ). The larger reduction in marriage and divorce rates in Mexico may be due to several factors, the most notable being the limited supply of vaccines, the weak economic relief response of the Mexican government, as well as limited administrative capacity of the government.…”
Section: Literaturementioning
confidence: 82%
See 2 more Smart Citations
“…Our findings in Mexico, a middle-income setting, suggest a similar decline in new marriages and new divorces. However, Mexico’s decline in new marriages (54%) and divorces (43%) is substantial when compared with related studies in high-income countries, which range from a reduction in new divorces by 3% to 27% and new marriages by 10% to 14% (Fallesen, 2021 , Kim & Kim, 2021 , Komura & Ogawa, 2022 , Westrick-Payne et al, 2022 ). The larger reduction in marriage and divorce rates in Mexico may be due to several factors, the most notable being the limited supply of vaccines, the weak economic relief response of the Mexican government, as well as limited administrative capacity of the government.…”
Section: Literaturementioning
confidence: 82%
“…The majority of the existing literature studying the impact of the COVID-19 pandemic on marriage and divorce rates focuses on high-income settings. Fallesen ( 2021 ) use a monthly series of divorce filings in Denmark, and show that the filing rate was 7% lower during the pandemic. In Japan, Komura and Ogawa ( 2022 ) find that the pandemic-induced nationwide state of emergency caused the number of marriages and divorces (per 1000 population) to decline by 10% and 27%, respectively.…”
Section: Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Several scholars in the intimate relationship sciences have argued that the pandemic constitutes an extraordinary setting for studying the functioning of relationships given that the majority of couples were "locked inside the same home" (Fernandes et al, 2020), at least in countries that experienced national lockdowns. The direct (e.g., illness, death of loved ones and the fear of one's own mortality) and indirect (e.g., employment loss) consequences of the pandemic have been closely interconnected with couples' relationship quality and stability (Fallesen, 2021;Manning and Payne, 2021). We believe that understanding whether and how the pandemic and the quarantine measures have affected relationship quality is crucial.…”
Section: Introductionmentioning
confidence: 98%
“…Several previous studies have found the associations between the hardships of the Covid-19 pandemic and the couples’ relationship ( Fernandes et al, 2021 ; Pietromonaco & Overall, 2021 ; Schmid et al, 2021 ). Some studies found that divorce rates increased during the pandemic compared to before the pandemic ( Goodwin et al, 2020 ; Zhu et al, 2021 ), while others found that they decreased ( Fallesen, 2021 ; Kim & Kim, 2021 ; Manning & Payne, 2021 ).…”
Section: Introductionmentioning
confidence: 99%